Determinants of euro-denominated corporate bond spreads - Elizaveta Krylova (European Central Bank (ECB), 2016)
This paper computes time-varying indicators of the relative importance of different credit spread determinants, including rating, sector and country attribution as well as the coupon rate, maturity and liquidity on the basis of the comprehensive dataset of individual bonds. Additionally, it decomposes variances of rating-specific (country- and sector-specific) spread indices into the impacts of explanatory variables. Both cross-sectional and time series analyses confirm that the rating effect was the major driver of corporate bond spreads during the pre-crisis period, while the recent financial crisis was characterised by increased cross-country and cross-sector heterogeneity. The sector effects in corporate spreads together with the rating effects for high-rated and low-rated bonds are found to be more closely linked to default rates and stock indices, whereas the common effect also to be linked to business cycle conditions. The dataset also allows documenting a break-up in the existence of country ceilings for corporate bond ratings during the crisis.
Keywords: G12; C21; C22; E44; 330; corporate bond spreads; credit risk